Peacebuilding and security sector governance in Asia - Uesugi, Yuji (LIT, 2014)
Covering Indonesia, the Philippines, Thailand, Nepal, Sri Lanka, and Timor-Leste, the case studies in this book explore the relevance of security sector governance and reform for political transition, democratization, and peace-building in Asia. Examining the prospects for security sector governance within each case - through the lens of political reconciliation, government legitimacy, civil-military relations, and democratic accountability - the book examines issues of political will, local/national ownership, and the influence of external actors in domestic reform contexts.